The Effect of Exchange Rates on Exports in the Era of Global and Regional Value Chains - Rizke Dwi Setiyani; Sugiharso Safuan (Universitas Udayana, 2026)
The rise of global value chains (GVCs) has made the relationship between exchange rates and exports difficult to predict. The increased of imported raw materials used in production due to GVC causes disconnection between exchange rates and exports. However, global financial crisis (GFC) that occurred in 2007-2009 has caused trade patterns shifted from GVC to regional value chains (RVC). Using panel fixed effects method, this study analyzes the effects of GVC and RVC on the export elasticities to exports in the European Union and ASEAN in the pre and post GFC period. The results show that GVC has a significant effect on the relationship between exchange rates and exports in the European Union in both periods. Meanwhile, RVC only has a significant effect in the period after the GFC. These results indicate a shift from GVC to RVC in the European Union. On the other hand, neither GVC nor RVC had a significant effect in ASEAN in both periods.